Synaptic versus extrasynaptic NMDA receptor signalling: implications for neurodegenerative disorders - Hardingham, Giles E. (2010)
There is a long-standing paradox that N-methyl-D-aspartate receptors (NMDARs) can both promote neuronal health and kill neurons. Recent studies show that NMDAR-induced responses depend on the receptor location: stimulation of synaptic NMDARs, acting primarily through nuclear Ca(2+) signaling, leads to the build-up of a neuroprotective ‘shield’, whereas stimulation of extrasynaptic NMDARs promotes cell death. These differences result from the activation of distinct genomic programmes and opposing actions on intracellular signalling pathways. Perturbations in the balance between synaptic and extrasynaptic NMDAR activity contribute to neuronal dysfunction in acute ischaemia and Huntington’s disease and could be a common theme in the aetiology of neurodegenerative diseases. Neuroprotective therapies should aim to both enhance the effect of synaptic activity and disrupt extrasynaptic NMDAR-dependent death signalling.